2021
DOI: 10.1021/acsaem.1c02954
|View full text |Cite
|
Sign up to set email alerts
|

Free-Standing N, P Codoped Hollow Carbon Fibers as Efficient Hosts for Stable Lithium Metal Anodes

Abstract: Constructing 3D hosts has been verified to be an effective strategy to control Li plating/stripping behaviors. Herein, free-standing N, P codoped hollow carbon fibers (NPHCFs) are prepared and regarded as efficient host materials, which can provide more lithiophilic nucleation sites and more volume to accommodate the Li metal. scanning electron microscopy (SEM) images suggest that the Li metal is confined to both the interspace and the inside of hollow carbon fibers without uncontrollable Li dendrites. An init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…At the same time, high specific surface area can effectively decrease the regional electric field and promote stable and uniform Li plating. Yang's group [ 73 ] reported the fabrication of free‐standing N/P co‐doped hollow carbon fiber (NPHCFs) as an effective carrier for stabilizing LMA using hollow polypyrrole (PPy) fiber as a template. Benefiting from N/P co‐doped, NPHCFs hosts show improving lithiophilic ability with low Li nucleation overpotential.…”
Section: Lithiophilic Designmentioning
confidence: 99%
“…At the same time, high specific surface area can effectively decrease the regional electric field and promote stable and uniform Li plating. Yang's group [ 73 ] reported the fabrication of free‐standing N/P co‐doped hollow carbon fiber (NPHCFs) as an effective carrier for stabilizing LMA using hollow polypyrrole (PPy) fiber as a template. Benefiting from N/P co‐doped, NPHCFs hosts show improving lithiophilic ability with low Li nucleation overpotential.…”
Section: Lithiophilic Designmentioning
confidence: 99%
“…For instance, N and P codoped hollow carbon fibers not only provided more lithiophilic sites, but also provided a larger accommodation space for lithium metal volume variations. 98 Niu et al designed the amine-functionalized mesoporous CNFs, as shown in Figure 7a, the amine functional group improved the lithiophilicity of the CNFs, and the mesopores on the CNFs surface are always the preferred nucleation sites for Li + , thus achieving a self-smoothing LMA. 99 LMBs assembled using this composite LMA paired with commercial NMC622 and MNC811 (LiNi 0.8 Mn 0.1 Co 0.1 O 2 ) cathodes delivered large energy densities of 350−380 Wh kg −1 and long cycle lives up to 200 cycles.…”
Section: Inorganic Nanofiber Frameworkmentioning
confidence: 99%
“…Furthermore, the combination of heteroatom doping and pore structure in CNFs can provide better performance. For instance, N and P codoped hollow carbon fibers not only provided more lithiophilic sites, but also provided a larger accommodation space for lithium metal volume variations . Niu et al designed the amine-functionalized mesoporous CNFs, as shown in Figure a, the amine functional group improved the lithiophilicity of the CNFs, and the mesopores on the CNFs surface are always the preferred nucleation sites for Li + , thus achieving a self-smoothing LMA .…”
Section: Nanofibrous Materials For Frameworkmentioning
confidence: 99%
“…For example, a two-dimensional (2D) Cu substrate modified with a hollow carbon nanosphere layer, a hollow semigraphitic carbon-coated SiO x /C microsphere layer, and a three-dimensional (3D) Ni skeleton coated with onion-like carbon granules allowed for stable Li metal anodes. Furthermore, 3D porous carbon-based materials , and 3D frameworks formed by carbon fibers were prepared as 3D current collectors to stabilize Li metal anodes. Interestingly, a variety of carbon nanomaterials including carbon nanotubes and graphene were successfully used for fabricating stable Li metal anodes.…”
Section: Introductionmentioning
confidence: 99%